Analysis of Paralleling Limited Capacity Voltage Sources by Projective Geometry Method - Alexandr Penin (The Scientific World Journal)
The droop current-sharing method for voltage sources of a limited capacity is considered. Influence of equalizing resistors and load resistor is investigated on uniform distribution of relative values of currents when the actual loading corresponds to the capacity of a concrete source. Novel concepts for quantitative representation of operating regimes of sources are entered with use of projective geometry method.